Technological Innovation Inputs, Outputs and Performance: the moderating role of Family Involvement in Management - Diéguez-Soto, Julio; Manzanaque-Lizano, Montserrat; Rojo-Ramírez, Alfonso A. (My University, 2015)
The objective of this article is to study the relationship between R&D intensity and continuous technological innovation and between technological innovation outcomes and sustained firm performance. We also analyse the moderating role of family management in both relationships. The results show that R&D intensity has a positive effect on continuous technological innovation and family management moderates negatively this relationship. Our findings also suggest that the influence of the family management significantly contribute to improve the effect of the technological innovation on sustained performance. It seems that some family-managed firms characteristics (nepotism,…) could hinder the efficient conversion of R&D expenditures into continuous technological innovation outcomes, but once family-managed firms have obtained technological innovation outcomes, they become riskier and put all its social capital to work to improve the conversion of innovation outcomes into performance. Therefore, family involvement in management looks influence technological innovation efficiency.
Keywords: Empresas familiares; Family firms; Technological innovation; Performance